The Meaning and Importance of Genetic Relatedness: Fertility Preservation Decision Making Among Israeli Adolescent Cancer Survivors and Their Parents - Barlevy, Dorit; Elger, Bernice; Wangmo, Tenzin; Ash, Shifra; Ravitsky, Vardit (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2020)
Background: With multiple options available today to become a parent, how does the matter of genetic relatedness factor into adolescent cancer patients’ fertility preservation (FP) decision making? This study reports on and normatively analyzes this aspect of FP decision making. Methods: A convenience sample of Israeli adolescent cancer survivors and their parents were invited to participate in individual, semi-structured interviews. Results: In discussing the importance of genetic relatedness to future children or grandchildren, participants repeatedly brought up the interrelated issues of nature, normalcy, and personal identity. Regardless of preference or ambivalence for genetic relatedness, the majority of participants were aware of alternative parenting options and noted both their advantages and disadvantages. However, knowledge of alternative parenting options was not uniform. Conclusions: To ensure that adolescent patients and their parents make informed FP decisions that meet their personal goals and values, it is important for physicians to discuss alternative parenting options with them in a culturally sensitive manner. Greater credence also should be given to those who question the importance of genetic relatedness.